Investigacion sobre secado natural y solar de trozos de yuca con aire forzado con un ventilador - Ospina, B.; Valdivieso Garcia, Mauricio A.; Gómez G., Guillermo G. (International Center for Tropical Agriculture, 1990)
The natural and solar drying system of cassava chips using natural air forced through the product with the help of a fan is described. This process enables drying to occur in the least time possible without affecting chip quality; likewise, it is not expensive. The system consists of a rural drying bin, a fan, and a solar collector which is optional depending on the drying capacity of the natural air. Illustrations are provided of the system; tables included indicate the materials required and the costs of constructing the different components of the system. The costs of different attachments are also indicated as well as labor requirements. (CIAT)